Effect of Proprioceptive Exercises on Pain and Function in Non-Specific Chronic Neck Pain (Medical Forum Monthly, 2022)
Objective: To determine the effect of proprioceptive exercises on pain and function in Non-specific chronic neck pain.Study Design: Randomized control trialPlace and Duration of Study: This study was conducted at the Muhammad physical therapy clinic and rehabilitation center, Multan from June 2020 to January 2021 for a period of one and a half year.Materials and Methods: Through non-probability convenient sampling technique 34 participants with chronic Non-specific neck pain were randomized in two groups through lottery method. Group A received conventional treatment with proprioception exercises while Group B received conventional treatment only. Pain and disability were measured by using numeric rating pain scale and Neck disability index scales were respectively. Exercise regime distributed in six weeks period alternate session in week exercise, 10-12 repetitions with 1-minute rest interval, and lasted 45 minutes in both groups. Pre-treatment and post-treatment measurements were taken.Results: Mean age for treatment group and control group was 31.85±4.94 and 30.85±6.93 years respectively. Mean of numeric rating pain scale in treatment group before treatment was 2.71±0.48 and post treatment mean was 0.85±0.37, p value was 0.00. In control group pretreatment mean of numeric rating pain scale was 2.71±0.48 and post treatment mean 1.85±0.37, p value was 0.001. For treatment group pretreatment mean for neck disability score was 4.28±0.75 and post treatment mean was 1.57±0.53, p value was 0.00. In control group pretreatment means neck disability score was 4.28±0.75 and post treatment was 3.28±0.75, p value was 0.04.Conclusion: Proprioceptive exercises were effective on improving pain and function in non-specific chronic neck pain.